KONSTRUKTIVISME DAN PEMBELAJARAN MATEMATIKA - Rangkuti, Ahmad Nizar (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2014)
Constructivism is a branch of philosophy which views knowledge as result of construction within human himself. He constructs knowledge through interaction with object, phenomena, experience and environment. Knowledge is considered true if it owns significance for problem solving. Learning in the view of constructionist offers to develop concept and perception from the students themselves. In the classroom process, teacher takes roles as moderator and facilitator. A constructivist teacher required to understand the characteristics of students’ mistakes due to that knowledge improvement is through mistakes and errors. Teacher must view mistakes as source of information about students’ characteristics scheme and thinking. There are four principles of constructivism in mathematics learning. First, psychological structure must be previous to occupation of number. Second, background knowledge structure (schemata) must be developed before teaching mathematics formal symbols. Third, students must possess opportunities for finding and forming their own mathematics relations, not to expose to adult thought. Fourth, teacher must create thinking atmosphere in the classroom.